2013
DOI: 10.1002/app.39976
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective optimization design of heating system in electric heating rapid thermal cycling mold for yielding high gloss parts

Abstract: An optimization design method is developed for the electric heating system in rapid thermal cycling molding (RTCM) mold. First, a multiobjective optimization model is established, in which the distance between the mold cavity surface and the center of heating elements and the number and power density of heating elements are the design variables, the required heating time t h and the highest cavity surface temperature T max at time t h are the objective functions. Then, an optimization strategy consisting of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Here, RSM [6,20] was applied to specify the effects of each heating rod power density on cavity surface temperature of the RHCM. The mathematical model of the expected responses for optimization was built through numerical experiment design and regression analysis [12,24].…”
Section: Optimization Processmentioning
confidence: 99%
“…Here, RSM [6,20] was applied to specify the effects of each heating rod power density on cavity surface temperature of the RHCM. The mathematical model of the expected responses for optimization was built through numerical experiment design and regression analysis [12,24].…”
Section: Optimization Processmentioning
confidence: 99%
“…Mold thermal response performance refers to mold heating efficiency and cavity surface temperature uniformity, which are two important technical indicators of RTCM [4]. In this section, a numerical simulation method was adopted to evaluate the mold thermal response performance, and some influencing factors were then analyzed and discussed.…”
Section: Evaluation Of Mold Thermal Response Performancementioning
confidence: 99%
“…Mold temperature is one of the most important process parameters for polymer processing, because it directly affects the quality of molded parts. It has been widely demonstrated that higher mold temperature cannot only effectively improve the surface appearance [1][2][3][4] and mechanical strength [5] of molded parts, but also greatly increase the flow length of thin-wall parts [6] and replication fidelity of micro-and nano-structure on plastics parts [7,8]. However, higher mold temperature will extend the molding cycle and thus decrease the productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced mold designs and manipulators have been developed to reduce the cycle time below 30 s at the price of more complex and expensive mold fabrication methods and less thermal control of the mold surface. These involves heating of the stamper material itself by electrical (Joule heating) [26][27][28] or induction heating [29,30].…”
Section: Introductionmentioning
confidence: 99%